Management and innovation for the artisans of Cuetzalan Puebla - Gamboa - Gochis, Ana Luisa; Osorio - Moranchel, Helder (Universidad Francisco de Paula Santander, 2021)
The International Development Bank (IDB) in 2013 referred to three aspects, creativity, arts and culture as rawmaterials; intellectual property rights, in particular with copyright, and direct insertion in the value chain; postulatethat strengthens the identity of indigenous peoples, who contribute to the local, national and international economyin particular the state of Puebla, Mexico, where the current municipal management 2018-2021 promotes the textilecraftsmanship of hand embroidery, waist loom and jonote fiber as a product of its creation and preservation of theculture of the place. From the coordination of promotion to the artisan generate interaction with them to strengthen their economic activity considered as the third of importance of the place, management and innovation as variables in this study will be analyzed to detect their relationship. It is an ongoing research, of mixed type for convenience where a pilot test was applied to 40 artisans to evaluate the influence of thes variables for the development of the handicrafts in the elaboration of their textile crafts in Cuetzalan Puebla, with the first results sociodemographic data are identified as well as their relationship with the dimensions and indicators of the variables.